Re-Conceiving Information Studies: A Quantum Approach - Budd, John M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This presentation is a suggestion for rethinking future inquiry in information studies. Features of quantum theory, including examining information and informing action as non-local, dynamic, and time-reversible allow for a departure from existing intellectual constraints. The result desired would be a renaissance in the examination of complex processes, examination not limited by past materialist, instrumentalist, and static conceptions. Cette communication propose une nouvelle façon de penser un questionnement futur en science de l’information. Des notions de théorie quantique, y compris examiner l’information et éclairer les interventions dans une optique non locale, dynamique et réversible permettent de s’éloigner des contraintes intellectuelles actuelles. Le résultat souhaité serait une renaissance de l’examen de processus complexes, non limité aux anciennes conceptions matérialistes, instrumentalistes et statiques.